Relationship Between Rheumatoid Arthritis and Periodontitis - Mercado, F.B.; Marshall, R.I.; Klestov, A.C.; Bartold, P.M. (Journal of periodontology (1970), 2001)
Background: Because of several similar features in the pathobiology of periodontitis and rheumatoid arthritis, in a previous study we proposed a possible relationship between the two diseases. Therefore, the aims of this study were to study a population of rheumatoid arthritis patients and determine the extent of their periodontal disease and correlate this with various indicators of rheumatoid arthritis. Methods: Sixty‐five consecutive patients attending a rheumatology clinic were examined for their levels of periodontitis and rheumatoid arthritis. A control group consisted of age‐ and gender‐matched individuals without rheumatoid arthritis. Specific measures for periodontitis included probing depths, attachment loss, bleeding scores, plaque scores, and radiographic bone loss scores. Measures of rheumatoid arthritis included tender joint analysis, swollen joint analysis, pain index, physician's global assessment on a visual analogue scale, health assessment questionnaire, levels of C‐reactive protein, and erythrocyte sedimentation rate. The relationship between periodontal bone loss and rheumatological findings as well as the relationship between bone loss in the rheumatoid arthritis and control groups were analyzed. Results: No differences were noted for the plaque and bleeding indices between the control and rheumatoid arthritis groups. The rheumatoid arthritis group did, however, have more missing teeth than the control group and a higher percentage of these subjects had deeper pocketing. When the percentage of bone loss was compared with various indicators of rheumatoid arthritis disease activity, it was found that swollen joints, health assessment questionnaire scores, levels of C‐reactive protein, and erythrocyte sedimentation rate were the principal parameters which could be associated with periodontal bone loss. Conclusions: The results of this study provide further evidence of a significant association between periodontitis and rheumatoid arthritis. This association may be a reflection of a common underlying disregulation of the inflammatory response in these individuals. J Periodontol 2001;72:779‐787.